KUALITAS PELAYANAN MASYARAKAT PADA KANTOR CAMAT PEULIMBANG KABUPATEN BIREUEN - Abu Bakar; M. Yusuf; Afriana Afriana (Fakultas Ekonomi Universitas Almuslim Bireuen, 2024)
Community services within the scope of sub-district apparatus duties at the sub-district office are starting to be reformed. From citizenship services to empowerment. And this requires work ability, work commitment, or supportive work culture conditions. This is the subject of this research, taking a case at the Peulimbang District Head's office, Bireuen Regency. The research was carried out in an associative descriptive manner, with a sample of 96 people who came to write a letter of recommendation for making KTPs, Family Cards, etc. at the Peulimbang District Head Office, Bireuen Regency. As a result of the research, information was obtained that the public's perception of the ability aspect of Plimbang sub-district office employees was good (88%), work commitment aspects reached 73.4% and work culture 80.05%. With the path analysis model approach, it is proven that there is a direct and indirect influence on work ability, organizational commitment and work culture, respectively 56.53%, 55.15% and 51.29% on the quality of community services. Simultaneously work ability, work commitment and work culture contribute to service quality by 70.8%